Analgesic Effect of Intermittent Multiple IPACK Block Combined with ACB in Patients with Flexion Contracture Knee Arthritis Undergoing Total Knee Arthroplasty - Ren, Yuqi; Hou, Zhouhui; Zhang, Yue; Li, Yue; Liu, Huanqiu (The Journal of Knee Surgery, 2025)
We aimed to compare the analgesic effects of intermittent multiple infiltrations between the popliteal artery and capsule of the posterior knee (IPACK) combined with adductor canal block (ACB) and intermittent ACB alone in patients with flexion contracture knee arthritis undergoing total knee arthroplasty (TKA). Forty-six patients who underwent elective unilateral TKA were divided into two groups (n = 23 each): intermittent multiple IPACK combined with ACB (group IA) and intermittent multiple ACB (group A). ACB was performed with 20 mL of 0.375% ropivacaine in each group and IPACK with 20 mL of 0.25% ropivacaine in group IA. Intermittent multiple nerve blocks were used for postoperative analgesia (IPACK block combined with ACB in group IA and ACB in group A between 7:30 and 8:30 a.m. on postoperative day 1 [POD1] and postoperative day 2 [POD2]). Primary outcomes assessed were pain at rest, motion-evoked pain (MEP), and range of motion (ROM) on POD1 and POD2. Secondary outcomes included opioid consumption, first ambulation time, ambulation distance, and postoperative complications. We observed that compared with group A, MEP decreased, ROM became wider, ambulation distance was longer, and opioid consumption decreased in group IA. Other outcomes were either similar between the groups or showed clinically insignificant differences. We conclude that multiple intermittent IPACK therapy combined with ACB provides superior analgesia than multiple intermittent ACB therapy alone in patients with flexion contracture knee arthritis undergoing TKA.
Keywords: IPACK; adductor canal block; total knee arthroplasty; flexion contracture; postoperative analgesia